Cellular organization of cardenolide biotransformation in Digitalis grandiflora Mill. - Kreis, Wolfgang; Hoelz, Hubert; Sutor, Renate; Reinhard, Ernst (Planta, 1993)
The cellular compartmentalization of cardenolide biotransformation in Digitalis grandiflora Mill. cell cultures was investigated. The presence of UDP-glucose: digitoxin 16′-O-glucosyltransferase (DGT; EC 2.4.1.-), acetyl-CoA: digitoxin 15′-O-acetyltransferase (DAT; EC 2.3.1.-) and cardenolide 16′-O-glucohydrolase (CGH; EC 3.2.1.21) was demonstrated and their time courses during one cell culture cycle were established. The activities of DGT, DAT and CGH were quite constant over time and leveled off at around 3, 30 and 100 ukat, respectively, per kg protein. The cardenolide products formed by DGT action were shown to be exclusively localized in the central vacuole. The cellular distributions of DGT, CGH and unspecific β-glucosidase were investigated and it was shown that DGT and CGH are not localized in the vacuoles, whereas unspecific glucosidase is. The influence on cardenolide uptake of the set of biotransformation enzymes present in a given cell line is discussed. An updated cellular model of cardenolide biotransformation is proposed. © 1993 Springer-Verlag.
UnivIS-Import:2015-03-05:Pub.1993.nat.dbio.LPB.cellul
Keywords: Acetylesterase; Acetyltransferase; Biotransformation; Cardiac glycoside (compartmentalization); Digitalis; Glucosyltransferase; Vacuole